Experimental comparison of dynamic responses of CO2 transcritical power cycle systems used for engine waste heat recovery. (1st April 2018) - Li, Xiaoya; Shu, Gequn; Tian, Hua; Huang, Guangdai; Liu, Peng; Wang, Xuan; Shi, Lingfeng
Highlights: Experimental comparison of dynamic response of four CTPC systems. Effects of mass flow rate and pressure ratio on dynamic performance are focused. Time constant and settling time are used to quantify dynamic characteristics. PR-CTPC possesses the fastest dynamic responses. Basic CTPC system responds four times faster than basic R123 ORC system. Abstract: CO2 transcritical power cycle (CTPC) is attractive to engine waste heat recovery (WHR) due to its advantages of miniaturization and unique thermophysical properties of its working fluid. Since there is no, if any, literature considering dynamic characteristics of CTPC systems, in current work, a series of dynamic tests has been conducted on a kW-scale CTPC test bench for engine WHR. Effects of mass flow rate and pressure ratio on dynamic responses are mainly focused and compared among four CTPC systems, i.e. a basic CTPC (B-CTPC), a CTPC with a recuperator (R-CTPC), a CTPC with a preheater (P-CTPC) and a CTPC with both a recuperator and a preheater (PR-CTPC). Dynamic characteristics are quantified by time constant and settling time. Results show that the PR-CTPC system has the fastest dynamic responses among these four layouts and the P-CTPC system responds more quickly than the R-CTPC system thanks to the gas–liquid heat exchange. Moreover, for the same layout, larger initial CO2 mass flow rate brings faster responses while initial system pressure ratio has little impacts on system dynamic responses. Also, dynamic characteristics of a basic CTPC system and a basic organic Rankine cycle (ORC) system are compared. The ORC system adopts R123 as its working fluid. Results indicate the basic CTPC system responds almost four times faster than the basic R123-ORC system.